Acute kidney injury in neonatal intensive care unit and the significance of nRIFLE criteria on diagnosis and prognosis - Coşkun, Çağrı; Buyan, Necla; Türkyılmaz, Canan; Atalay, Yıldız; Bakkaloğlu Ezgü, Sevcan Azime (The European Research Journal, 2024)
Objectives: The objective of this study is to identify factors that affect the severity of acute kidney injury (AKI) using neonatal RIFLE (Risk, Injury, Failure, Loss of function, End-stage kidney disease) criteria; to identify the impact of these criteria and the factors on mortality rates and to determine the one-year clinical outcome. Methods: Five hundred and thirty-two inpatients who were admitted to Gazi University, Faculty of Medicine, Neonatal Intensive Care Unit (NICU) between 2006 and 2016 have been examined retrospectively. Results: Acute kidney injury developed in the first month of life in 85 (16%) patients. Thirty-nine (7.35%) of the cases were term and 46 (8.65%) were preterm. Among these patients, 33 (38.8%) were in the risk group, 18 (21%) in the injury group, and 34 (40%) in the failure group. Metabolic acidosis and edema were the most commonly seen findings as acute kidney injury scores increased. According to the neonatal RIFLE (nRIFLE) criteria, the severity of AKI was significantly correlated (p < 0.05) with metabolic acidosis (71%) and edema (50.5%). There was a positive correlation between urinary output and pH, bicarbonate, glomerular filtration rate, and sodium values in patients with AKI, while a negative correlation between urinary output and BUN, creatinine, potassium, phosphorus, and uric acid was found. Regarding the nRIFLE criteria, the frequency of hyponatremia and hyperpotassemia was increased as the AKI severity score was increasing (p < 0.05). The mortality rate was 54% in the newborn period and factors that significantly affect mortality were the need for mechanical ventilation, sepsis, nephrotoxicity, and acidosis (p < 0.05). Conclusions: The nRIFLE criteria based on urinary output is a guide for clinicians to diagnose AKI. There is a need to work on new markers in future studies.